Penggunaan Metode Demontrasi Dalam Peningkatan Hasil Belajar Siswa pada Standar Kompetensi Mengukur Besaran Listrik Rangkaian Elektronika - Oo Sugiarto (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
This study aims to improve student learning outcomes on competency standards Mengukur Besaran Listrik Rangkaian Elektronika with the Demonstration method. The research method used was classroom action research with 2 cycles. Each research cycle includes planning, implementing, observing and reflecting. The research subjects used were grade X students of Industrial Electrical Engineering 4 SMK 1 Cirebon. The results showed that the demonstration method used with the media can improve student learning outcomes because it can foster student self-confidence and can increase student understanding of the material being taught. Giving praise to students during learning can motivate students to learn so that student activity in learning increases. Providing guided training to students who have difficulty completing training during teaching and learning activities can increase learning activities of students of Class X Electrical Engineering Industry 4 SMK N 1 Cirebon City.